Is forest certification targeting areas of high biodiversity in cork oak savannas? - Dias, Filipe S.; Bugalho, Miguel N.; Orestes Cerdeira, J.; João Martins, M. (Biodiversity and Conservation, 2012)
Over the last four decades the world has been losing biodiversity at an alarming rate despite the increasing number of protected areas (PAs). Certiﬁed forest management may complement the role of PAs in protecting biodiversity. Forest certiﬁcation aims to promote sustainable forest management and to maintain or enhance the conservation value of certiﬁed forests. The area of forest under certiﬁed forest management has grown quickly over the past decade. Forest Stewardship Council (FSC) certiﬁcation, for example, currently covers 148 million hectares, i.e., 3.7 % of the world’s forests. In spite of such increase there is, however, a dearth of information on how forest certiﬁcation is related to biodiversity. In this study we assessed if FSC certiﬁcation is being applied in high biodiversity areas in cork oak savannas in Portugal by comparing biodiversity values of certiﬁed and non-certiﬁed areas for birds, reptiles and amphibians. We calculated the relative species richness and irreplaceability value for each group of species in certiﬁed and non-certiﬁed areas and compared them using randomization tests. The biodiversity value of certiﬁed areas was not signiﬁcantly greater than that of non-certiﬁed areas. Since FSC certiﬁcation is expanding quickly in cork oak savannas it is important to consider the biodiversity value of these areas during this process. Prioritizing areas of high biodiversity value would enhance the conservation value of forest certiﬁcation and facilitate integrating certiﬁcation with other conservation initiatives.
Keywords: Biodiversity conservation; Conservation strategies; Forest management; Irreplaceability; Mediterranean; Species richness